ANALISA STABILITY DAN MOTION TERHADAP PENYEBAB TERBALIKNYA KMP. BILI DI DERMAGA TEBAS SEBERANG, KALIMANTAN BARAT - Tsaniya Az Zahra (2022)
The accidents experienced by Bili Ferry while serving on Tebas Kuala - Tebas Seberang, West Kalimantan in 2021 caused capsized by 90˚ at the destination dock. This study aims to determine the cause of the ship capsized through stability and motion analysis. Ship modeling using Maxsurf Modeller, stability analysis using Maxsurf Stability, and analysis of the ship's motion for surfe and roll using ANSYS AQWA Hydrodynamic Diffraction and Response. Based on the results of inclining test, at 5˚ of heel the maximum GZ values is 4,26 m, 10˚ of heel the maximum GZ values is 2,58 m, 15˚ of heel the maximum GZ values is 1,13 m. Ship motion simulation depicts that surge has the most significant average value with 1,797 m in 0˚ and 180˚ wave directions, while roll in 90˚ wave direction with average value of 5,039 m. Meanwhile, river flow velocity simulation shows that surge has the largest value at Fn 0,421 with 0,727 for each wave direction and roll has the highest value at Fn 0,421 with -0,003 m for each wave direction. The main cause of the capsized was the ingress of water which caused the lifting moment to decrease due to the ship's inability to expel water through the insufficient freeing port.